2019
DOI: 10.1186/s12966-019-0790-9
|View full text |Cite
|
Sign up to set email alerts
|

Device-measured physical activity, sedentary behaviour and cardiometabolic health and fitness across occupational groups: a systematic review and meta-analysis

Abstract: Background With approximately 8 hours of one’s waking day spent at work, occupational tasks and environments are important influencers on an individual’s physical activity (PA) and sedentary behaviours. Little research has compared device-measured physical activity, sedentary behaviour and cardiometabolic outcomes between occupational groups. Objective To compare device-measured movement (sedentary time [ST], light intensity physical activity [LPA], moderate-to-vigorous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
108
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 174 publications
(61 reference statements)
9
108
0
4
Order By: Relevance
“…We are not aware of any other large-scale investigation examining a combination of several health risk indicators in different high-resolution occupational groups. Though, the physical activity patterns at work and in leisure time in the present study are partly similar to previous reports in both major occupational groups and in some sub-major groups (9,10,21). For example, white collar/professional occupations are consistently reported to have a higher amount of leisure time moderate-to-vigorous physical activity compare to blue collar workers (4,21), with less differences in leisure time sitting (22,23).…”
Section: Single Risk Indicators In Occupational Groupssupporting
confidence: 88%
See 1 more Smart Citation
“…We are not aware of any other large-scale investigation examining a combination of several health risk indicators in different high-resolution occupational groups. Though, the physical activity patterns at work and in leisure time in the present study are partly similar to previous reports in both major occupational groups and in some sub-major groups (9,10,21). For example, white collar/professional occupations are consistently reported to have a higher amount of leisure time moderate-to-vigorous physical activity compare to blue collar workers (4,21), with less differences in leisure time sitting (22,23).…”
Section: Single Risk Indicators In Occupational Groupssupporting
confidence: 88%
“…As these are heterogeneous groups of occupations with a diversity of work situations that could have an effect on health outcomes. For instance, previous reports have indicated variations in overweight, smoking and occupational physical activity between a larger range of occupational groups (9,10,8). Other studies found differences in physical activity but con icting results of cardiorespiratory tness between occupational groups (9,11).…”
Section: Introductionmentioning
confidence: 97%
“…Nurses are the largest occupational group in Canada's health system including 282,300 publicly employed nurse managers and registered nurses (Infometrica Limited, 2017). Although nursing is perceived to be a physically active occupation, nurses have been found to spend more than half their time being sedentary on work days and very few achieve current physical activity guidelines (at least 150 min per week of moderate-to-vigorous intensity physical activity (MVPA) in bouts of 10 min or more) (Shields & Wilkins, 2006;Ratner & Sawatzky, 2009;Tremblay et al, 2011;Reed et al, 2018;Prince et al, 2019). Nurses working rotating shifts rarely obtain optimal amounts of sleep (i.e., at least 7 h) and have greater odds of reporting fair or poor health when compared to nurses who work days only (Shields & Wilkins, 2006;Rogers, 2008;Edward, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review found that of 132 unique trials (N¼15,619 participants), on average, workers accumulated 8124 steps per day. 16 One of the primary driving factors in the number of steps per day was the type of work perfomed (eg, postal delivery 16,100 steps vs office workers 6857 steps). To improve physical activityfor staff in our workplace, we conducted a study to determine whether we could improve workplace activity at our medical facility using a wearable activity tracker and combining brief feedback using individualized activity goals.…”
mentioning
confidence: 99%